Interpretable Machine Learning Reveals Dissimilarities Between Subtypes of Autism Spectrum Disorder - Garbulowski, Mateusz; Smolinska, Karolina; Diamanti, Klev; Pan, Gang; Maqbool, Khurram; Feuk, Lars; Komorowski, Jan (Frontiers in Genetics, 2021)
Autism spectrum disorder (ASD) is a heterogenous neuropsychiatric disorder with a complex genetic background. Analysis of altered molecular processes in ASD patients requires linear and nonlinear methods that provide interpretable solutions. Interpretable machine learning provides legible models that allows explaining biological mechanisms and supports analysis of clinical subgroups. In this work, we investigated case-control studies of gene expression measurements of ASD individuals. We constructed a rule-based learning model from three independent datasets that we further visualized as a non-linear gene-gene co-predictive network. To find dissimilarities between ASD subtypes, we scrutinized topological structure of the network and estimated a centrality distance. Our analysis revealed that autism is the most severe subtype of ASD, while Pervasive Developmental Disorder-Not Otherwise Specified and Asperger Syndrome are closely related and milder ASD subtypes. Furthermore, we analyzed the most important ASD-related features that were described in terms of gene co-predictors. We found a strong co-predictive mechanism between EMC4 and TMEM30A, that may suggest an interaction between these genes. The present study demonstrates the potential of applying interpretable machine learning in bioinformatics analyses. Although the proposed methodology was designed for transcriptomics data, it can be applied to other omics disciplines.